1993
DOI: 10.1017/s0020818300027934
|View full text |Cite
|
Sign up to set email alerts
|

The International Labor Organization and the welfare state: institutional effects on national welfare spending, 1960–80

Abstract: National welfare programs are importantly affected by models of welfare activity institutionalized at the global level. This article examines the impact of the welfare regime advocated by and within the International Labor Organization (ILO). Countries that have recently ratified ILO conventions related to welfare show increased growth in spending, net of national characteristics. Subanalyses show that the effects of ILO ratification are strong in the industrialized capitalist democracies, particularly where p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
22

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 187 publications
(122 citation statements)
references
References 33 publications
2
98
0
22
Order By: Relevance
“…may become advocates for a given policy, providing seemingly disinterested and objective analysis of its benefits+ Students of epistemic communities postulate that policy professionals, academics, international nongovernmental organizations INGOs!, and NGOs can influence governments to adopt new policies simply by making arguments for them+ 85 Epistemic communities not only help to define new solutions to existing problems~for example, central bank independence as a solution to inflation! but also identify new problems and propose solutions to them~for example, global warming and the Kyoto protocols!+ The epistemic community of American economists is often seen to have played a critical role in economic liberalization in Latin America and beyond+ 86 It may be that Latin American countries sent economics students to the University of Chicago because they wanted, ex ante, to join the liberal bandwagon driven by Friedman and colleagues+ This would suggest that North American economists had an effect on Latin American economic policies, but that their influence operated through the preferences of national leaders who sent deputy finance ministers to train in the United States, rather than through the preferences of newly minted Chicago School graduates themselves+ Either way, the community of economists has arguably shaped new policy norms+ Whereas conventional logic-of-development arguments suggest that countries will adopt certain programs when they are developmentally ready for them, world polity theorists have found that countries embrace new norms for symbolic reasons, even when they cannot begin to put them into practice+ This is particularly true of social welfare policies and human rights+ Strang and Chang, for example, find that large numbers of countries ratified International Labor Organization treaties guaranteeing welfare rights, but that only in developed countries did ratification lead to increased welfare expenditures+ Developing countries signed the treaty even though they lacked the resources to carry through+ This may not represent bad faith so much as the power of new international norms even in countries that are not developmentally capable of implementing them+ 87 Even in the realm of 83+ See Finnemore and Sikkink 2001;Ruggie 1998;and Wendt 1999+ 84+ Haveman 1993+ 85+ See Haas 1959Mintrom 1997;and Mintrom and Vergari 1998+ 86+ Numerous studies have purported to show, for example, the influence of "Chicago boys" in economic policy change in Latin America, either directly or indirectly+ See Drake 1994;Harberger 1997;Montecinos 1997;andMurillo 2002+ 87+ Strang andChang 1993+ economic policy, countries may adopt new global norms before they are really ready+ The other principal emulation approach draws on reference group theory in social psychology+ From this perspective, individuals emulate the behavior of their selfidentified peers, even when they cannot ascertain that doing so will in fact be in their best interests+ At the international level, sociocultural linkages~common language, history, religion, and so on! may contribute to "psychological proximity" among nations+ 88 Indeed, many cross-national analy...…”
Section: Emulationmentioning
confidence: 99%
“…may become advocates for a given policy, providing seemingly disinterested and objective analysis of its benefits+ Students of epistemic communities postulate that policy professionals, academics, international nongovernmental organizations INGOs!, and NGOs can influence governments to adopt new policies simply by making arguments for them+ 85 Epistemic communities not only help to define new solutions to existing problems~for example, central bank independence as a solution to inflation! but also identify new problems and propose solutions to them~for example, global warming and the Kyoto protocols!+ The epistemic community of American economists is often seen to have played a critical role in economic liberalization in Latin America and beyond+ 86 It may be that Latin American countries sent economics students to the University of Chicago because they wanted, ex ante, to join the liberal bandwagon driven by Friedman and colleagues+ This would suggest that North American economists had an effect on Latin American economic policies, but that their influence operated through the preferences of national leaders who sent deputy finance ministers to train in the United States, rather than through the preferences of newly minted Chicago School graduates themselves+ Either way, the community of economists has arguably shaped new policy norms+ Whereas conventional logic-of-development arguments suggest that countries will adopt certain programs when they are developmentally ready for them, world polity theorists have found that countries embrace new norms for symbolic reasons, even when they cannot begin to put them into practice+ This is particularly true of social welfare policies and human rights+ Strang and Chang, for example, find that large numbers of countries ratified International Labor Organization treaties guaranteeing welfare rights, but that only in developed countries did ratification lead to increased welfare expenditures+ Developing countries signed the treaty even though they lacked the resources to carry through+ This may not represent bad faith so much as the power of new international norms even in countries that are not developmentally capable of implementing them+ 87 Even in the realm of 83+ See Finnemore and Sikkink 2001;Ruggie 1998;and Wendt 1999+ 84+ Haveman 1993+ 85+ See Haas 1959Mintrom 1997;and Mintrom and Vergari 1998+ 86+ Numerous studies have purported to show, for example, the influence of "Chicago boys" in economic policy change in Latin America, either directly or indirectly+ See Drake 1994;Harberger 1997;Montecinos 1997;andMurillo 2002+ 87+ Strang andChang 1993+ economic policy, countries may adopt new global norms before they are really ready+ The other principal emulation approach draws on reference group theory in social psychology+ From this perspective, individuals emulate the behavior of their selfidentified peers, even when they cannot ascertain that doing so will in fact be in their best interests+ At the international level, sociocultural linkages~common language, history, religion, and so on! may contribute to "psychological proximity" among nations+ 88 Indeed, many cross-national analy...…”
Section: Emulationmentioning
confidence: 99%
“…In the two-stage model of institutionalization, the emergence of new paths or fields is a 'bottom up' phenomenon: (1) organizations or states adopt structures or policies in response to local problems, politics or characteristics, which then spark (2) processes of mimesis, theorization and diffusion, eventually crystallizing a broader community of practice around a core set of principles or models (Tolbert & Zucker 1983;Baron, Dobbin, & Jennings 1986;Galaskeiewz & Wasserman 1989;Strang & Chang 1993). As solutions diffuse, they become taken-for-granted as an accepted norm, serving as baselines to which organizations must subsequently conform as a condition for legitimacy.…”
Section: Movements From Outside Institutions: Challenger/ Dominance Amentioning
confidence: 99%
“…Acculturation involves "social costs" such as shaming or shunning as distinct from the more material costs associated with overt coercion. These pressures may lead to superficial compliance with international norms as reflected in treaty obligations, not necessarily the internationalization of norms as deeply held values (Strang & Chang 1993). The socialization literature theorizes the diffusion of norms over time and space, but it is still puzzling as to why some norms seem to be internalized and complied with more than others.…”
Section: Theoretical Approaches To Treaty Violation and Compliancementioning
confidence: 99%